Karakteristik Hadis Tentang Pendidikan dan Kewirausahaan - Hendri Happy Firdaus (Journal of Public Policy Analys, 2024)
This study examines the characteristics of hadiths on education and entrepreneurship from an Islamic perspective. Education in Islam is not only a transfer of knowledge, but also a process of forming good character, morals, and ethics. Hadiths related to education emphasize the importance of seeking knowledge and fostering good manners as the main foundation of life. On the other hand, hadiths on entrepreneurship provide guidance on Islamic ethics and principles in running a business, such as honesty, independence, creativity, and courage in taking risks. Entrepreneurship in Islam is seen as a means to achieve worldly success based on religious values, without neglecting spiritual responsibilities. This study uses a textual analysis method on a number of relevant hadiths, showing that the two aspects 'education and entrepreneurship' are inseparable in Islamic teachings. The integration of the two produces individuals who are not only materially successful, but also have noble morals. Thus, these hadiths provide important guidance for Muslims to develop their potential, both in education and the business world, in order to achieve blessings and common good. The results of this study reveal the importance of hadith in shaping the character and ethics of a Muslim through education and entrepreneurship. The main findings include: (1) Islamic education is not only the transfer of knowledge, but also the formation of morals; (2) entrepreneurship as a means of practicing Islamic principles with creativity, courage, and honesty; (3) the balance of the world and the hereafter in entrepreneurial activities; (4) the relevance of hadith in the modern era supports the concept of edupreneurship; (5) the importance of creativity and innovation in entrepreneurship.